Low-cost plasmonic solar cells prepared by chemical spray pyrolysis - Kärber, Erki; Katerski, Atanas; Oja Acik, Ilona; Mikli, Valdek; Mere, Arvo; Sildos, Ilmo; Krunks, Malle (Beilstein Journal of Nanotechnology, 2014)
Solar cells consisting of an extremely thin In2S3/CuInS2 buffer/absorber layer uniformly covering planar ZnO were prepared entirely by chemical spray pyrolysis. Au nanoparticles (Au-NPs) were formed via thermal decomposition of a gold(III) chloride trihydrate (HAuCl4·3H2O) precursor by spraying 2 mmol/L of the aqueous precursor solution onto a substrate held at 260 °C. Current–voltage scans and external quantum efficiency spectra were used to evaluate the solar cell performance. This work investigates the effect of the location of the Au-NP layer deposition (front side vs rear side) in the solar cell and the effect of varying the volume (2.5–10 mL) of the sprayed Au precursor solution. A 63% increase (from 4.6 to 7.5 mA/cm2) of the short-circuit current density was observed when 2.5 mL of the precursor solution was deposited onto the rear side of the solar cell.
Keywords: Au nanoparticles; chemical spray pyrolysis; extremely thin absorber; plasmon resonance; solar cell